Barrier Potential, Structure (Monomer and Dimer), Inter- and Intra-Molecular Interactions, Vibrational Analysis, Fukui Functions, MESP, NBO, UV and NMR Analysis of Pyridine-3-Carboxylic Acid Using Spectroscopic and DFT Approach. (16th March 2023) - Ramesh, G.; Reddy, B. Venkatram
Abstract: Pyridine-3-carboxylic (or nicotinic) (P3CA) acid has been recorded by using different spectroscopic tools like NMR ( 13 C, 1 H), UV–Vis, FT-IR and FT-Raman spectral analysis. The structural conformation examined by potential energy scan for the titled compound was obtained by using DFT computations through B3LYP method with 6–311++G(d, p) basis set. Using optimized monomer structure, the dimeric structures (head-to-tail and tail-to-tail) are obtained. The title compound exhibits inter-molecular as well as intra-molecular hydrogen bonding forming a supramolecular network. The geometrical parameters of both monomer and dimer are coinciding with the observed ones. Using vibrational frequencies, Infrared and Raman intensities were computed. The rms error between the experimental and scaled quantum mechanical frequencies is 9.77 cm −1 for P3CA. From the scaled quantum mechanical method, reliable vibrational assignments were made using PED. The site of chemical reactivity and selectivity of the title compound were estimated from frontier molecular orbitals and local reactivity descriptors. The reactive areas around the compound were evaluated by using MESP. The interactions of donor and acceptor are studied by NBO analysis. The 13 C and 1 H NMR chemical shifts of the title compound were determined using the gauge independent atomic orbital (GIAO) method in DMSO- d 6 solution. By using UV–visible spectrum, the maximum absorption wavelength was obtained and compared with the TD-DFT method. Graphical Abstract: UF0001